2021
DOI: 10.3389/ffgc.2021.688851
|View full text |Cite
|
Sign up to set email alerts
|

Soil Organic Carbon Stocks in Mixed-Deciduous and Coniferous Forests in Austria

Abstract: Question: We compared the soil organic carbon stock of the forests of an entire country. The objective of our research was establishing the differences between coniferous or deciduous forests with respect to soil carbon stocks. The question is relevant because coniferous forests are increasingly damaged by abiotic and biotic disturbances that are related to climate change. Deciduous forests are considered to be less vulnerable. Their soils are expected to be more persistent and reliable sinks for carbon dioxid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 51 publications
4
8
0
Order By: Relevance
“…Germany's National Forest Soil Inventory (NFSI) has shown that pine forests have significantly higher C stocks in the soil organic layer than beech and other deciduous forests but lower stocks in the mineral soil (Grüneberg et al, 2019). Similar results regarding carbon stocks were found in the Austrian Forest Soil Survey but without differences in their vertical gradients (Jandl et al, 2021). Reasons for this included different lignin contents and C/N ratios; moreover, litter from leaves and needles differ in decomposability, resulting in different SOC stocks in the organic layer and mineral soil, as well as in different humus forms and chemistry (Fischer et al, 2002;Leuschner et al, 2013;Vesterdal et al, 2013;Diers et al, 2021).…”
Section: Introductionmentioning
confidence: 67%
“…Germany's National Forest Soil Inventory (NFSI) has shown that pine forests have significantly higher C stocks in the soil organic layer than beech and other deciduous forests but lower stocks in the mineral soil (Grüneberg et al, 2019). Similar results regarding carbon stocks were found in the Austrian Forest Soil Survey but without differences in their vertical gradients (Jandl et al, 2021). Reasons for this included different lignin contents and C/N ratios; moreover, litter from leaves and needles differ in decomposability, resulting in different SOC stocks in the organic layer and mineral soil, as well as in different humus forms and chemistry (Fischer et al, 2002;Leuschner et al, 2013;Vesterdal et al, 2013;Diers et al, 2021).…”
Section: Introductionmentioning
confidence: 67%
“…The effect also holds for the traditional Austrian beech mixtures, such as beech/spruce [117,118], beech/oak [119], beech/pine [120], and spruce/fir/beech [121]. Effects on soil carbon will, in general, also be similar to a change from spruce to beech when admixing beech into previously pure conifer forests [80,122]. The high competitiveness of beech results in the need for more intensive management in order to keep high-value timber from other trees.…”
Section: Deadwoodmentioning
confidence: 92%
“…(1) ECC (16) where G i , G represent the GDP of the ith county-level city and the whole region; C i , C represent the carbon emissions of the ith county-level city and the whole region. The coefficient is used to measure the contribution of regional carbon emissions and the economy.…”
Section: Construction Of Carbon Compensation Zoning Modelmentioning
confidence: 99%
“…Terrestrial ecosystems absorbed a net 31% of the carbon dioxide released by human activities over the same period from 2010 to 2019 [15]. The methods for calculating carbon sinks include the sample site inventory method [16], the eddy covariance method [17], the ecosystem process modeling method [18], the atmospheric inversion method [19]. With the rapid development of remote sensing in recent years, scholars often utilize land use data to estimate carbon sinks at different scales.…”
Section: Introductionmentioning
confidence: 99%